Design Help Desk System Using GSM Modem for Call Centre in the Automobile Industry - Waidah Ismail; Dalilah Abdullah; Rizal Razali; Idris Osman (2024)
2nd International Conference on Solid State Science and Technology 2006, 4 – 6 September 2006.